2009
DOI: 10.1186/1471-2458-9-172
|View full text |Cite
|
Sign up to set email alerts
|

Association of parents' alcohol use and family interaction with the initiation of alcohol use by sixth graders: A preliminary study in Taiwan

Abstract: Background: The family is the main environment where children are socialized and learn individual behavior. Although previous studies have examined predictors of preadolescent first alcohol use, few studies have analyzed factors associated with alcohol use in children in a country with low alcohol consumption. The aim of this study was to investigate the initiation of alcohol use by sixth graders and determine family factors associated with first alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 41 publications
4
39
2
7
Order By: Relevance
“…27,28,35,39 Likewise, parental alcohol use is shown to be a risk factor for pre-adolescent use of alcohol. 10,40 Moreover, low levels of parental monitoring are reported to be a risk factor for general substance use initiation in pre-adolescence. [41][42][43] Our Study.…”
Section: Other Predictors Of Pre-adolescent Initiation To Risk Takingmentioning
confidence: 99%
“…27,28,35,39 Likewise, parental alcohol use is shown to be a risk factor for pre-adolescent use of alcohol. 10,40 Moreover, low levels of parental monitoring are reported to be a risk factor for general substance use initiation in pre-adolescence. [41][42][43] Our Study.…”
Section: Other Predictors Of Pre-adolescent Initiation To Risk Takingmentioning
confidence: 99%
“…13, no 2, décembre 2014 Fleming et al, 2002 ;Hung et al, 2009 ;Kandel et al, 1999 ;Kaplow et al, 2002 ;King et al, 2004 ;Wills et al, 2002). Bien que ces différentes études ne soient pas spécifiques aux jeunes qui présentent des troubles de comportement, il est tout de même possible d'affirmer que les caractéristiques associées à une initiation précoce chez les jeunes de la population générale pourraient être transposées à une clientèle d'enfants traités pour troubles de comportement.…”
Section: Discussionunclassified
“…Pour certains auteurs, chez des enfants de 10 ans, les facteurs familiaux seraient les facteurs influençant le plus l'initiation précoce aux psychotropes (Macleod, Hickman, Bowen, Alati, Tilling et Smith, 2008). D'abord, la consommation de cigarettes et d'alcool par les parents (principalement la mère) est un facteur de risque important permettant de prédire l'expérimentation de la cigarette et de l'alcool au cours de la préadolescence (Fleming et al, 2002 ;Hung, Yen et Wu, 2009 ;Kaplow et al, 2002 ;Macleod et al, 2008 ;Martel et al, 2009). Ce lien peut être interprété de différentes manières.…”
Section: Facteurs Familiauxunclassified
See 1 more Smart Citation
“…The perception of healthy or unhealthy behaviours in parents may stimulate their children to initiate healthy or unhealthy behaviours. For example, Hung, Yen, and Wu (2009) showed that having parents who both used alcohol was a significant predictor of sixth graders' first alcohol use. Our study showed that Parental Monitoring was associated with both the Health and the Delinquency cluster.…”
Section: Conclusion and Discussionmentioning
confidence: 99%